The Utilization of International Subscription E-Journals in Supporting Research on Stunting (INCH : Journal of Infant and Child Healthcare, 2024)
This study investigates the utilization of international e-journals for stunting-related research at Poltekkes Kemenkes Riau. The purpose is to uncover insights into how students interact with international e-journals about stunting, identify challenges, and assess the librarian's role in promoting awareness. Employing in-depth interviews, the research gathers data thematically to gain a profound understanding of these dynamics. The findings highlight students' limited familiarity with international e-journals, primarily due to language barriers and a lack of guidance. However, librarians play a pivotal role in fostering awareness of these resources. The study concludes by emphasizing the significance of collaboration between librarians and students, supported by initiatives aimed at enhancing access and language proficiency. This collaborative approach holds the potential to invigorate the use of international e-journals for stunting-related research and contributes to the broader knowledge domain.